The state of blacks in higher education - Darity, William A
This is a study initiated by the National Association for Equal Opportunity in Higher Education (NAFEO) that provides an overview on the state of blacks in higher education from 1986 through 2005. It focuses on bachelor’s, master’s, and doctorate degrees earned by black Americans. It also examines the advancement, or lack thereof, of black faculty members. The study uses data from the Integrated Postsecondary Education Data Series and the Survey of Doctorial Recipients.blacks; higher education;